Digital governance and civic inclusion to enhance public participation in political decision-making processes - Sadat, Anwar (Frontiers in Political Science, 2025)
IntroductionDigital transformation has significantly influenced public governance, requiring new approaches to accountability, transparency, and participatory decision-making. This study explores how digital innovation reshapes governance quality and public participation through institutional and behavioral mechanisms, emphasizing the interaction between dynamic capabilities and policy design.MethodsA quantitative design using structural equation modeling (SEM) was applied to data collected from 412 respondents across local government agencies. Measurement validity and reliability were confirmed through confirmatory factor analysis (CFA). Model fit indices indicated an excellent level of structural consistency.ResultsFindings reveal that digital innovation (DIR) significantly improves e-government service quality (EGSQ) and positively affects participatory public policy decision-making (PPPDM), which in turn enhances digital leadership (DL). The mediating effects of PPPDM and EGSQ strengthen the indirect relationship between DIR and DL, supporting the theoretical framework.DiscussionThe study contributes to the literature by integrating digital governance and socio-technical perspectives into a single explanatory model. The results highlight the importance of participatory mechanisms and leadership adaptability in achieving sustainable digital governance outcomes. Practical implications suggest that governments should invest in digital literacy and participatory infrastructures to reinforce accountable and transparent governance.